STUDENTS’ ABILITY IN DEVELOPING SENTENCES IN ENGLISH PARAGRAPH WRITING - Zulfah, Nanning, dan Mujahidah . (Al-Ishlah: Jurnal Pendidikan Islam, 2015)
This research focused in analyzing students’ ability in developing paragraph by accounting the number of sentence quality or comprehensibility of paragraph by analyzing sentence unity and coherence. This research is quantitative-qualitative research. The subject of the research was the fifth semester students of English Education Study Program. Instrument of data collection is test. Quantitative data was analyzed by using frequency formulation and qualitative data about the unity and the coherence of sentences was analyzed by using coding. Thus, the finding shows that the most students are able to write two to three sentences in a paragraph. Paragraphs consist of one sentence and two sentences were indicated as poor paragraph. Paragraph consists of four, five, six and seven sentences were indicated as fairly good paragraph; and paragraph consists of three and eight sentences were indicated as good paragraph.